Hubungan Dukungan Suami dengan Pencegahan Sekunder Kanker Serviks pada Wanita Usia Subur - Wipradnyani, Ni Made Shinta; Surinati, I Dewa Ayu Ketut; Hartati, Ni Nyoman; Runiari, Nengah; Suratiah, Suratiah; Suardani, Ni Luh Ketut; Labir, I Ketut; Sipahutar, Ida Erni (Jurnal Gema Keperawatan, 2025)
Cervical cancer is one of the diseases that often affects women. Efforts can be made to prevent cervical cancer through secondary prevention, either by IVA examination or Pap smear. Secondary prevention is influenced by the support of husbands, as they play an important role in encouraging women to undergo secondary prevention for cervical cancer. This study aims to determine the relationship between husband support and secondary prevention of cervical cancer. The research design used was an analytical correlation with a cross-sectional approach. The research sample consisted of 130 women of childbearing age, and the research instrument was a questionnaire on spousal support, which included emotional support, instrumental support, informational support, and evaluative support, with a validity test result of 0,601 0,361. This study used consecutive sampling. The type of data used was primary data. The results showed that 63,9% of women of childbearing age received high levels of support from their husbands, and 48,5% of women of childbearing age had undergone secondary prevention of cervical cancer. The chi-square test results obtained a p-value = 0,000 (p0,05) and a correlation value using Cramer's V with a value of 0,73, which means that spousal support has a strong correlation with secondary prevention of cervical cancer in WUS. The conclusion of this study is that there is a relationship between spousal support and secondary prevention of cervical cancer among women of childbearing age at the UPTD Puskesmas Kediri II Tabanan. To facilitate secondary prevention of cervical cancer, the researchers recommend conducting educational programs on the importance of undergoing examinations.